2012
DOI: 10.1016/j.bcp.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

p23 co-chaperone protects the aryl hydrocarbon receptor from degradation in mouse and human cell lines

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-sensitive transcription factor which is responsible for most 2,3,7,8-tetrachlorodibenzo-p-dioxin toxicities. Without ligand, the AhR complex is cytoplasmic and contains p23. Our objective was to investigate whether the wild type p23 levels are important for the AhR function. We generated eight p23-specific knockdown stable cell lines via either electroporation or lentiviral infection. Five of these stable cell lines were generated from a mouse hepatoma cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…The best known mechanisms that trigger the AHR proteasomal degradation are mediated through binding of a ligand [21] and treatment with an Hsp90 inhibitor such as geldanamycin [22]. In addition, we have reported that down-regulation of p23 causes degradation of the AHR protein in various mouse and human cell lines [23]. Here we present data supporting that this p23 effect is not merely changing the dynamics of the AHR cytoplasmic complex.…”
Section: Introductionsupporting
confidence: 70%
“…The best known mechanisms that trigger the AHR proteasomal degradation are mediated through binding of a ligand [21] and treatment with an Hsp90 inhibitor such as geldanamycin [22]. In addition, we have reported that down-regulation of p23 causes degradation of the AHR protein in various mouse and human cell lines [23]. Here we present data supporting that this p23 effect is not merely changing the dynamics of the AHR cytoplasmic complex.…”
Section: Introductionsupporting
confidence: 70%
“…1A). In the cytoplasm, the ligand-free AHR is in a complex with two HSP90 molecules, at least one p45 protein identified as an immunophilin [10, 11], and the co-chaperone p23 protein [12]. In canonical AHR signaling, ligand binding alters the complex allowing the translocation of the AHR to the nucleus and partnering with the aryl hydrocarbon nuclear translocator (ARNT).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted similar gel shift experiment which we routinely performed to observe the ligand-dependent formation of the AHR gel shift complex from nuclear extracts and the baculovirus expressed AHR and ARNT proteins [22, 23]. Results from the gel shift assay showed that GA-hAHR can effectively form a gel shift complex with GA-hARNT in a ligand-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%